Clipping Technique for BER and PAPR Reduction in OFDM System (International Journal of Engineering and Computer Science, 2015)
Peak to Average Power Ratio (PAPR) is one of most detrimental aspects in any wireless communicationsystem using multicarrier modulation technique like OFDM, which cause power degradation and spectralspreading. Due to the simplest way for PAPR reduction, clipping technique has been proposed and seems tobe promising for use in commercial system. In this paper, we mainly focus on Amplitude clipping andfiltering method. Later in this paper, simulation result shows the PAPR and BER performance with clippingand filtering with different clipping ratios. The BER of the original OFDM signal is approximateatSNR = 10 dB. With clipping, BER is increased to just higher thanat the SNR = 10dBandtheBERperformance improves a little bit with filtering.